Analysis of Teacher Ethics in The Learning Process - Ulfa Barus, Khairu; Najwa, Adinda (International Journal of Students Education, 2023)
Ethics is something that educators must pay attention to, because applying ethics during the teaching and learning process creates a pleasant and conducive learning atmosphere. Teachers who have good ethics will make their students respect teachers and will apply these ethics. As a teacher, you must carry out your obligations as a teacher. Teachers also have a teacher’s code of ethics, where the code of ethics aims to provide guidance and the teacher’s views in carrying out the learning process. Teachers are expected to have abilities such as asking questions, providing learning motivation to students, managing the class so that it is conducive and enjoyable and creating various types of learning. Education has an indispensable role in shaping the characteristics of students through a learning process that really requires knowledge, experience, understanding and information conveyed by an educator. Learning is a learning process in which students can explore their potential so that it can be developed. Learning is very important to determine the direction of students’ development in the school environment and learning with current technology which is widely provided as a learning resource. Learning is a stage in changing a person’s habits and behavior. In the learning process, teachers must have ethics when teaching, namely straightening out intentions, starting with something good, behaving well, educating gradually according to age, protecting oneself from useless things, being serious, and maximizing potential. Work as a teacher is work that must be done professionally. This research aims to find out how a teacher’s ethics are in the teaching and learning process, which focuses on the teaching and learning process. Where teachers must be professional in teaching students. Teachers are people who are able to carry out their duties and obligations fully and teachers have abilities that can be appreciated in carrying out their duties and responsibilities.